Salt-free and low temperature colouration of silk using He–N2 non-thermal plasma irradiation. (10th May 2021) - Teli, M.D.; Pandit, Pintu; Samanta, Kartick K.; Basak, S.; Gayatri, T.N.
Abstract: A natural protein fibre (silk), in the form of textile, was subjected to a non-thermal plasma irradiation in a mixture of helium/nitrogen (He–N2 ) gases by varying the nitrogen (N2 ) gas flow rates at atmospheric pressure. After 4 min He–N2 plasma irradiation, the silk fabric was found to be more hydrophilic in nature in terms of decrease in time of water absorbency. A similar improvement was also noticed with an increase in both the plasma irradiation time and N2 gas flow rate. The scanning electron micrographs (SEM) of the treated samples depicted the etching of fibre surface and occurrence of micro-pits and craters. The energy dispersive X-ray (EDX) elemental analysis depicted maximum 2.2% and 2.9% increase in oxygen (O2 ) and nitrogen (N2 ), respectively owing to plasma-induced chemical change in the silk protein fibre. Mass spectroscopy results also exhibited an improvement in amine, amide, imine and other polar groups in the plasma irradiated samples, which caused them to be dyeable with acid dye without usage of salt, even at a much lower temperatures of 40 °C and 60 °C compared to conventionally used 90 °C. The rate of dyeing in the plasma pre-irradiated silk was found to improve more than 50% and 30% compared to that of the untreated silk fabric dyed at 40 °C and 60 °C, respectively. The improvements in dye absorption, dye-fixation, and colour strength were measured in details with variable gas flow rates and correlated with the changes in surface physico-chemical properties of silk polymer. It is postulated that the enhancement in surface roughness along with formation of hydrophilic groups on the fibre surface contributed towards the observed improvements. In the plasma treated dyed samples, colour stability towards the washing, rubbing and light exposure was 1–2 grades higher as compared to that in case of untreated sample. The proposed low-temperature and salt-free process will economise the cost of colouration of silk fabric, besides reducing the effluent load. Graphical abstract: Image 1 Highlights: Plasma irradiation helps in reducing dyeing temperature by 30–50 °C. Plasma assisted acid dyeing of silk without usage of salt. Higher dye exhaustion, fixation and deeper shade in treated samples. Reduction in dyeing time for similar dye exhaustion. Better colour stability towards washing, rubbing and light exposure.